KONFLIK TANAH HIBAH MASYARAKAT NELAYAN DENGAN PEMERINTAH KABUPATEN ACEH BARAT - Nurlian Nurlian (Prodi Sosiologi FISIP Universitas Teuku Umar, 2018)
These conflicts arise because people demanded compensation for land area of 16.1 hectares that has been occupied for six months as a substitute homeland of the fishing community in the village of Padang Seurahet due West Aceh District Government states that the land area of 16.1 hectares located in the village of Pasie Pinang is Government land. Buildings constructed on this land if the Sports and Arts (GORS). The purpose of this study to determine the root causes of conflict and ways of conflict resolution sociology, namely Negotiation, Mediation and Conciliation. The theory used is George Simmel conflict theory and Lewis Coser.untuk REMEDY conflict analysis used the concept of conflict resolution negotiation, mediation and conciliation in the paradigm of sociology. Qualitative research methods were used to obtain research data. The research found that, the Government of West Aceh found, can not be compensated on the ground because it does not do grant legally to the public and the public has been getting its due in the relocation of another tsunami, a native lands in the village of Padang Seurahet been replaced by land and houses in the permanent housing aid donors. Conflict settlement initially reached by way of negotiation and conciliation by the Government of West Aceh District, but did not find the solution, so that the final resolution adopted by law (litigation). Keywords: Land Conflict, Government, Fishermen Society and Conflict Resolution